Does the Disposition Effect Matter in Corporate Takeovers? Evidence from Institutional Investors of Target Companies. (7th April 2014) - Ye, Pengfei
Abstract: This paper examines whether one of the most important participants in the takeover market, the institutional investors of target companies, suffers from the disposition effect and, if so, how this selling bias influences the takeover outcomes. I report robust evidence that target institutional investors are reluctant to realize losses. This bias further allows their sunk cost to affect both the takeover price and the deal success. My results are explained by neither the undervalued targets nor the 52-week-high price effect. They are most pronounced among targets whose investors have a strong propensity to hold on to loser stocks.